Commercial conspiracy theories: a pilot study - Furnham, Adrian (Frontiers in Psychology, 2013)
There are many ways to categorise conspiracy theories. In the present study, we examined individual and demographic predictors of beliefs in commercial conspiracy theories among a British sample of over 300 women and men. Results showed people were cynical and sceptical with regard to advertising tricks, as well as the tactics of organisations like banks and alcohol, drug and tobacco companies. Beliefs sorted into four identifiable clusters, labelled sneakiness, manipulative, change-the-rules and suppression/prevention. The high alpha for the overall scale suggested general beliefs in commercial conspiracy. Regressions suggested that those people who were less religious, more left-wing, more pessimistic, less (self-defined as) wealthy, less Neurotic and less Open-to-Experience believed there was more commercial conspiracy. Overall the individual difference variables explained relatively little of the variance in these beliefs. The implications of these findings for the literature on conspiracy theories are discussed.